EcoPopulism : toxic waste and the movement for environmental justice - Szasz, Andrew, 1947- (Social movements, protest, and contention, 1994)
This book reconstructs the growth of a powerful movement around the question of toxic waste, following the issue as it moves from the world of "official" policymaking in Washington, onto the nation's television screens and into popular consciousness, and then into America's neighborhoods, spurring the formation of thousands of local, community-based groups. Szasz shows how, in less than a decade, a rich infrastructure of more permanent social organizations emerged from this movement, expanding its focus to include issues like municipal waste, military toxics, and pesticides. In its s